COMPARISON OF MACROZOOBENTHOS COMMUNITY STRUCTURE ON SEAGRASS ECOSYSTEMS IN THE WATERS OF NIRWANA COAST AND PULAU PANJANG OF WEST SUMATRA - Julians, Rizky Fajar; Nasution, Syafruddin; Nursyirwani, Nursyirwani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Macrozoobenthos have various roles in the ecosystem, one of which is as a biological indicator because macrozoobenthos will react to disturbances in an aquatic ecosystem. Seagrasses are breeding and sheltering grounds for marine life, one of which is macrozoobenthos. Nirwana Beach and Pulau Panjang are waters that have seagrass ecosystems in West Sumatra. The purpose of this study was to compare the community structure of macrozoobenthos in the waters of Nirwana Beach and Pulau Panjang, this research was conducted in the waters of Nirwana Beach and Pulau Panjang in June-July 2021. The method used in this study is the survey method; sampling was carried out using three plots on each transect with a size of 1m x 1m and was repeated three times on each plot. The results of this study found that the abundance value in the waters of Nirwana Beach was 20.59 ind/m2 and in the waters of Pulau Panjang 21.44 ind/m2, the diversity index (H’) in the waters of Nirwana Beach was 2.450 and in the waters of Pulau Panjang was 2.680, The uniformity index (E) in the waters of Nirwana Beach is 0.738 while in the waters of Pulau Panjang, it is 0.807 and the dominance(C) in the waters of Nirwana Beach is 0.162 and in the waters of Pulau Panjang is 0.198. The distribution pattern (Id) of macrozoobenthos at both locations is clustered with a value of 1.07 ind/m2 in the waters of Nirwana Beach and 1.13 ind/m2 in the waters of Pulau Panjang. The community similarity index was categorized as moderate with 66% at both study sites.